THE ROLE OF PLACEMENT FACILITIES AND PLACEMENTS IN THE DEVELOPMENT OF TOURISM IN THE JIZZAKH REGION - Abdiramanov, Zhangabay Bektursinovich; Usmanov, Mashrab Rustamovich; Abdinazarova, Khidoyatkhan Oripovna (SCIENCE and SOCIETY, 2026)
This article presents proposals and recommendations on the role of tourism in the world, tourism, the unique nature and unique historical monuments of the Jizzakh region, architectural monuments, as well as resolutions and decrees on tourism development, archaeological monuments located in the region, architecture (historical monuments, pilgrimage sites) and monumental and attractive places, hotels, mountainous and lowland areas of the region, accommodation facilities, hotel, family guest houses, tourism company activities, tourist routes of the Bakhmal district, projects in the field of tourism, tourism prospects.
Keywords: Tourism; geographical location of the region; resolutions and decrees on tourism development; number of archaeological monuments; architectural (historical monuments, pilgrimage sites) and monumental attractions; gastronomic tourism; hotel; family guest houses; travel company; tourist routes and tourism prospects